Medieval literature 1300-1500 - King, Pamela M. (Edinburgh critical guides to literature., 2011)
Medieval literature can be daunting. This critical guide is designed to help readers to relax in the company of diverting and entertaining voices from that 'other country' that is the past. Medieval Literature 1300-1500 offers close readings of Middle English texts placed within the culture with which they interact. Famous works, like The Canterbury Tales, are discussed alongside lesser-known poems, prose, and plays, in five thematically-organised chapters, accompanied by helpful critical apparatus. Reflecting the proliferation of user-friendly editions, many available on-line, this book extends the range of Middle English writing for which there is accessible up-to-date critical support, enabling the student, the general reader, the course designer, and the aspirant specialist, to read widely and with enjoyment in the medieval period. Key Features Offers succinct close-readings of well-known texts of the period Provides cultural-historical background to England in the Middle Ages Reflects on the construction of an English literary 'tradition' Cross-references literary texts against historical events and other art forms